Violência, cidadania e medo: vivências urbanas em Fortaleza - Matos Júnior, Clodomir Cordeiro de (2008)
This work is intended as a contribution to studies that are dedicated to understanding the ways to try and live in urban contexts. Investigating ways to appropriate and relate socially in neighborhoods marked by violence and fear, Fortaleza was revealed from the viewpoint of the residents of Aerolândia. The urban space seen through the prism of insecurity poses interesting questions to think about the exercise of citizenship as social practices. In societies of mass and of comsumptions the assertion of individuality, identity and visions of the world pass through a visible imagery difficult to be carried in dangerous contexts. View the fruits of a successful inclusion in the democratic society of consumption is raised as a problematic task when the public space is assessed from the point of view of the increase in crime. Thinking of citizenship not as abstract category, but as an element accessed in the context of the practices and social relations are proving to be the complex experiences of democratic marginalized urban masses. Citizenships are practiced, not possessed.